Implant strategies for finishing calves - C.T. Milton; Robert T. Brandt Jr.; Gerry L. Kuhl; P.T. Anderson (Kansas Agricultural Experiment Station Research Reports, 1996)
Two hundred-sixteen Angus and Angus-cross steer calves (690 lb) were used in a 129- day finishing study to evaluate different implant strategies, including an experimental new implant for feedlot cattle that contains 28 mg of estradiol benzoate and 200 mg of trenbolone acetate (EBTBA). Treatments were 1) nonimplanted control, 2) implanted and reimplanted with Synovex-Sfi, 3) single initial implant with EBTBA, 4) single initial implant with Revalor-Sfi, 5) implanted with Synovex-S and reimplanted with EBTBA, and 6) implanted and reimplanted with EBTBA. Initial implants and reimplants were administered on day 0 and 63, respectively. All implant treatments increased feed intake, slaughter and carcass weights, and rate and efficiency of gain. Compared with other implant treatments, the use of EBTBA as a reimplant treatment (trts 5 and 6) resulted in improved (P<.08) rate and efficiency of gain and heavier carcass weights (P<.07). However, only 58.3% of cattle in trts 5 and 6 graded Choice vs. 86.1% for controls and 80.6% for steers implanted twice with Synovex-S (P<.07). Carcasses were more masculine (P<.07) for steers in trts 5 and 6 than for nonimplanted controls, steers implanted with Revalor-S, and steers implanted twice with Synovex-S. Performance of steers implanted once with EBTBA did not differ from that of steers implanted once with Revalor-S or twice with Synovex-S, but carcasses were more masculine (P<.07) for EBTBA vs. Revalor-S steers. Implant treatment did not affect meat tenderness, as measured by Warner-Bratzler shear force determinations. Single EBTBA or Revalor-S implants resulted in performance and carcass traits similar to those resulting from implanting twice with Synovex-S.
Keywords: Cattlemen& #x27; s Day; 1996; Kansas Agricultural Experiment Station contribution; no. 96-334-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 756; Beef; Implant; Estradiol; Trenbolone acetate; Steers